Plant Diversity and Quantitative Characteristics Of Wetland Community on the North Bank of Hanjiang River in Cheng GU, Shaanxi Province, China - Li, Zongwu; Zhang, Yi; Li, Fujing; Duan, Mengge (Bangladesh Journal of Botany, 2023)
Four water ecological surveys were carried out on the north bank of Hanjiang river in two seasons from 2020 to 2021. Based on the field wetland quadrat survey and literature data, the species diversity index was determined. The research showed that there are 360 species of wetland plants belonging to 108 families and 264 genera on the north bank of Hanjiang river, and the geographical composition of seed plants is at the genus level, mainly temperate distribution types, with 160 species. In the community species diversity index, the mean value of Patrick index was 18.80 ± 5.19. The mean Shannon Wiener diversity index was 2.15 ± 0.39. The mean value of Simpson dominance index was 0.81 ± 0.10. The average Pielou evenness index was 0.75 ± 0.10. The mean value of Margalef index was 3.44 ± 0.87. The Patrick index and Margalef index of the Bidens pilosa form were the lowest. The Shannon-Wiener diversity index，the Simpson index，and the Pielou index of the Potamogeton malaianus form were the lowest. The Patrick index of the Colocasia esculenta form was the highest,and the Pielou of the Sapium sebiferum form was the highest. The Shannon- Wiener diversity index and Simpson index of the Populus canadensis form group were the highest, and the Margalef index of the Flueggea virosa form was the highest. The research results provide basic data and scientific basis for the protection and restoration of wetland ecosystems and management of wetland resources in Yuan'an and similar areas. Bangladesh J. Bot. 51(4): 839-848, 2022 (December) Special